Perbuatan Melawan Hukum Yang Dilakukan Oleh Notaris/PPAT Dalam Transaksi Jual Beli Rumah Di Kabupaten Pesawaran (SOL JUSTICIA, 2023)
Notary/PPAT is a public official who has the authority from the State to assist the public in making the required authentic deed. Deeds are written agreements made before a Notary/PPAT. In carrying out their duties and authorities, a Notary/PPAT must always comply with all existing laws and regulations and uphold the dignity of a Notary/PPAT and adhere to the professional code of ethics. As a public official who has the authority to make authentic deeds, a Notary/PPAT has an important role for the community. As workers who work in the field of law, notaries/PPATs are not only required to understand how the mechanism for making authentic deeds, but notaries/PPATs must be trustworthy, wise and professional in carrying out their functions as public officials with authority. The results of this study indicate that there are still many loopholes that can be exploited by irresponsible notaries to gain profits in a fraudulent way, and it can be noted that there is a need for updates or additions to laws and codes of ethics governing the Notary/PPAT profession. so that there is no fraud that harms the community because of the ignorance of the community itself.